A Systematic Review of Teachers’ Perspectives on the Use of Grammarly in EFL Writing Classrooms - Sefina, Aurelya Chesia (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Grammarly has become increasingly popular among teachers and students as an automated writing evaluation tool for improving writing accuracy in English as a Foreign Language (EFL) contexts. Despite its widespread use, teachers’ perspectives on its pedagogical benefits and challenges in writing instruction remain an important area to explore. This study aims to examine EFL teachers’ perspectives on the use of Grammarly in writing classrooms, particularly focusing on its perceived benefits and challenges. A systematic literature review method was employed by analyzing 15 peer-reviewed journal articles published in national and international journals between 2020 and 2025. The articles were selected using specific keywords related to Grammarly and teachers’ perspectives and were retrieved from Google Scholar and SINTA databases. The selected studies were analyzed thematically to address two research questions concerning the benefits and challenges of using Grammarly in EFL writing classrooms. The findings indicate that Grammarly offers several benefits, including saving teachers’ time in providing written feedback, enhancing students’ grammatical accuracy, and improving overall writing quality. However, the review also reveals several challenges, such as students’ over-reliance on automated feedback, inaccuracies in correcting complex or context-dependent errors, and Grammarly’s limited ability to address higher-order writing concerns such as organization, coherence, and content development. These findings suggest that while Grammarly can serve as a supportive tool in EFL writing instruction, it should be used alongside teacher guidance and human feedback to ensure effective and balanced writing development. Directions for future research are also discussed.